TEACHING MEMORIES AS PART OF THE PROFESSIONAL TEACHER EDUCATION - de OLIVEIRA, Célia Zeri (2013)
The aim of this paper is to highlight the contributions of the memory in teachers for recognizing conceptions that underpin the practice of the teacher in the classroom. It also has as purpose to demonstrate the use of theoretical-methodological approaches that appropriate of memory resource can contribute to the apprehension of the factors that influence professional teacher education. Therefore, the research is supported by reflections on the importance of memory teaching and narrative about yourself (CIAMPA, 1998; CODO, 1992; BRAGANÇA, 2011), in order to analyze teachers testimonies collected in audio. In the course of the analysis, it was investigated memories about the teachers’ pedagogical activities, how the teachers perceive the student's learning process and, lastly, about self-reflection on their own activities. Thus, in general, the results reveal elements that point to the teacher reflection on the problem of teaching reading faced by the school, acceptance of the urgency to conduct educational activities that enable a dynamic interaction between teacher and learner in classroom, and appreciation of teaching experience and theoretical knowledge as part of the process that contributes to the teacher education.